THE INFLUENCE OF GIVING TEST REGULARLY TO IMPROVE STUDENT’S ACHIEVEMENT IN LEARNING ENGLISH - PANUSUNAN (English Study Program University of Pasir Pengaraian, 2016)
This article is concerned with the analysis of the influence of giving test regularly to improve the students’ achievement in learning English at grade VIII of state junior high school 14 of Tambusai Utara. The aspects explored in the study covered activities done by the students in their learning activities. Generally, all teachers such as English can conduct the giving test regularly. The research employed the descriptive quantitative design and the instruments used in collecting the data were a set of questionnaire and tests. The data analysis covered the use of product moment. The findings showed that use of giving test regularly better improved the students’ achievement at grade VIII of state junior high school 14 of Tambusai Utara.